2014
DOI: 10.1017/ipm.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Can the new epidemiology of schizophrenia help elucidate its causation?

Abstract: The supposed universality of the incidence and prevalence of schizophrenia has been seriously challenged. It is now widely accepted that the life-time prevalence and incidence of this disorder vary considerably in time and place. As a result, there has been renewed interest in environmental causation of schizophrenia. There are few extant formulations that have successfully integrated the available new evidence into a coherent theory for its causation. The outgroup intolerance hypothesis is an attempt to integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Schizophrenia is found worldwide in diverse cultures. Within a Western model of schizophrenia, this condition has been purported to be fundamentally similar across all cultures with the only difference in its content and form (33). However, this supposed universality of the incidence and prevalence of schizophrenia has been challenged (33).…”
Section: Cross-cultural Findings Of Language Disorder In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Schizophrenia is found worldwide in diverse cultures. Within a Western model of schizophrenia, this condition has been purported to be fundamentally similar across all cultures with the only difference in its content and form (33). However, this supposed universality of the incidence and prevalence of schizophrenia has been challenged (33).…”
Section: Cross-cultural Findings Of Language Disorder In Schizophreniamentioning
confidence: 99%
“…Within a Western model of schizophrenia, this condition has been purported to be fundamentally similar across all cultures with the only difference in its content and form (33). However, this supposed universality of the incidence and prevalence of schizophrenia has been challenged (33). The lifetime prevalence and incidence of this disorder varies significantly in time and place (33).…”
Section: Cross-cultural Findings Of Language Disorder In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Although OT failed to ‘normalize’ the response towards out-group individuals (especially the conflictual out-group) we have suggested that such a normalization may be feasible if patients were treated with OT at an early stage of their illness before the neuropathological changes have reached an advanced stage (Abed & Abbas, 2014). We hypothesized that treating the illness (with OT) at an early stage or treating ‘ultra-high-risk’ patients in the prodromal phase may offer a preventative strategy through ‘resetting the threshold’ for designating others within the social environment as in-group, thus rectifying what we consider to be the core psychopathological process that leads to the fully fledged syndrome of schizophrenia.…”
mentioning
confidence: 90%
“…We have proposed that in-group–out-group dynamics have aetiological significance in schizophrenia. We hypothesized that a sensitivity or intolerance towards out-group members resulting from an interaction between social environmental factors (abundance of out-group members in the social environment or paucity of contact with kin/in-group members or a combination of both) and individual characteristics (difficulty in re-assigning out-group individuals as in-group members or having a high threshold for designating individuals as in-group) results in dysregulation and aberrant connectivity in critical brain centres, leading to schizophrenia (Abed & Abbas, 2011, 2014).…”
mentioning
confidence: 99%